IDENTIFICATION AND METABOLIC ACTIVITIES OF BACTERIAL SPECIES BELONGING TO THE ENTEROBACTERIACEAE ON SALTED CATTLE HIDES AND SHEEP SKINS - (:unkn) unknown (AMER LEATHER CHEMISTS ASSOC, 2015)
The detailed examination of the Enterobacteriaceae on salted hides and skins offers important information to assess faecal contamination of salted hides and skins, its roles in hide spoilage, and efficiency of hide preservation. Hence, salted cattle hide and skin samples were obtained from different countries and examined. Total counts of Gram-negative bacteria on hide and skin samples, respectively, were 10(4)-10(6) and 10(5)-10(6) CFU/g; of Enterobacteriaceae 10(4)-10(5) and 10(5)-10(6) CFU/g; of proteolytic Enterobacteriaceae 10(3)-10(5) and 10(5)-10(6) CFU/g; of lipolytic Enterobacteriaceae 10(2)-10(5) and 10(4)-10(5) CFU/g; and of each species belonging to Enterobacteriaceae 10(2)-10(5) and 10(3)-10(5) CFU/g. Moisture contents of the hide (between 17% - 29%) and skin samples (between 18% - 39%) were low, and salt saturations of most hide and skin samples were fairly high (100%), but these microorganisms were isolated from the samples in high numbers. Although 16 bacterial species belonging to genera of Cedecea, Enterobacter, Escherichia, Ewingella, Klebsiella, Proteus, Raoultella, Serratia and Yersinia were isolated from the hide samples, 16 bacterial species belonging to genera of Citrobacter, Enterobacter, Escherichia, Klebsiella, Proteus, Raoultella, Serratia and Yersinia were isolated from the skin samples. These species were identified using API (R) 20E Test Kits. Although Cedecea lapagei, Serratia rubidaea and Yersinia enterocolitica were the most prevalent microorganisms on the hide samples, Escherichia coli, Serratia rubidaea and Serratia plymuthica were the most prevalent bacterial isolates on the skins. The most common bacterial species isolated from both hides and skins was Serratia rubidaea. The presence of the members of Enterobacteriaceae on the hides and skin samples in high numbers was evidence of faecal contamination and inadequate preservation. According to biochemical test results, isolates exhibited catabolic activity to break down carbohydrate, lipid and protein which may adversely affect leather quality. Hide and skin samples contain different species of Enterobacteriaceae which may cause deterioration of hides and skins; therefore, effective antibacterial applications should be applied to hides and skins to eradicate these microorganisms and prevent substantial economical losses in leather industry.
Keywords: ESCHERICHIA-COLI O157; SP-NOV; CARCASSES; GOATS